2018
DOI: 10.3390/sym10110572
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cobalt Catalyst Confinement in Carbon Nanotubes Support on Fischer-Tropsch Synthesis Performance

Abstract: Pre-treating the multi-walled carbon nanotubes (CNTs) support by refluxing in 35 vol% nitric acid followed by heating at the temperature of 600 to 900 °C resulted in the formation of defects on the CNTs. Increasing the temperature of the pre-treatment of the CNTs from 600 °C to 900 °C, enhanced the fraction of cobalt-oxide nanoparticles encapsulated in the channels of CNTs from 31% to 70%. The performance of Co/CNTs in Fischer-Tropsch synthesis (FTS) was evaluated in a fixed-bed micro-reactor at a temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 41 publications
3
30
0
Order By: Relevance
“…In addition, a significant amount of Co particles are confined in the inner cavity of the tubes (Figure d), which has already been observed for FTS with Co/CNT catalysts . The 15 %Co/CNF catalyst contains relatively large Co particles, which could be due to both low amount of surface oxygen groups and low specific surface area of this support . Some of these particles are confined in the inner cavity of CNF (Figure f).…”
Section: Resultssupporting
confidence: 57%
“…In addition, a significant amount of Co particles are confined in the inner cavity of the tubes (Figure d), which has already been observed for FTS with Co/CNT catalysts . The 15 %Co/CNF catalyst contains relatively large Co particles, which could be due to both low amount of surface oxygen groups and low specific surface area of this support . Some of these particles are confined in the inner cavity of CNF (Figure f).…”
Section: Resultssupporting
confidence: 57%
“…Prior to loading the metal catalyst to the CNT, functionalization and activation steps had to be conducted [14,15]. The aim of these steps was to enhance the interplay between the CNT support and the active catalyst sites.…”
Section: Purification and Functionalization Of Cnt Supportmentioning
confidence: 99%
“…The figures also show the presence of blockage on the CNT pores. Generally, it has been reported that the extent of the metal loading has a significant effect on the particle size and dispersion of the catalyst on the support, which, in turn, has an effect on the catalyst activity and selectivity [16][17][18][19][20][21][22]. Th reduction and activation of the resulting calcined catalyst is an important step prior to the catalytic performance reaction.…”
Section: Effect Of Co Loading On Catalyst Properties and Performancementioning
confidence: 99%